Pharmacotheraphy in chronic obstructive pulmonary disease - Celli, Bartolome R. (Lung biology in health and disease, 2004)
This volume considers the application of clinical assessment to the drug development process. Important topics include genetics and sleep-related breathing disturbances in COPD.